2018
DOI: 10.1016/j.jmoldx.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mutation and Loss of Heterozygosity by Whole-Exome Sequencing Yields Insights into Pseudomyxoma Peritonei

Abstract: Pseudomyxoma peritonei (PMP) is a clinical syndrome characterized by gross mucinous ascites originating from a disseminated intraperitoneal neoplasm. Although typically confined to the abdomen, mortality is high if untreated. Biomarkers, including genetic mutation profiles, may aid treatment selection and decision making. We applied whole-exome sequencing to five patients diagnosed with low-grade appendiceal mucinous neoplasms, using paired tumor and germline samples identify biomarkers. Multiple bioinformatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…An RNF43 stop-gained mutation in a region of LOH in a LAMN has recently been described [10]. In 5 LAMNs, a mutation signature consistent with deamination of 5-methylcytosine was commonly detected [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An RNF43 stop-gained mutation in a region of LOH in a LAMN has recently been described [10]. In 5 LAMNs, a mutation signature consistent with deamination of 5-methylcytosine was commonly detected [10].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies of PMP and AMTs are limited, but somatic mutations have been identified in KRAS (60-100% of sequenced cases), GNAS (30-74%), SMAD4 (16%), and TP53 (5-14%) [3][4][5][6][7][8][9]. Compared to colorectal cancer, somatic mutations in the APC gene are observed at a much lower frequency, ranging between 0 and 33% [4,7,9,10]. An RNF43 stop-gained mutation in a region of LOH in a LAMN has recently been described [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular studies of PMP and AMTs are limited, but somatic mutations have been identified in KRAS(60-100%) GNAS in (30-74%), SMAD4 (16%), and TP53 (5-14%) (3)(4)(5)(6)(7)(8)(9). Compared to colorectal cancer, somatic mutations in the APC gene are observed at a much lower frequency, ranging between 0-33% (4,7,9,10). An RNF43 stop-gained mutation in a region of LOH in a LAMN has recently been described (10).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to colorectal cancer, somatic mutations in the APC gene are observed at a much lower frequency, ranging between 0-33% (4,7,9,10). An RNF43 stop-gained mutation in a region of LOH in a LAMN has recently been described (10). In 5 LAMNs, a mutation signature consistent with deamination of 5-methylcytosine was commonly detected (10).…”
Section: Introductionmentioning
confidence: 99%